2018
DOI: 10.1097/md.0000000000012793
|View full text |Cite
|
Sign up to set email alerts
|

Intravascular large B-cell lymphoma presenting as multiple stroke

Abstract: Introduction:Intravascular large B-cell lymphoma (IVLBCL) is an uncommon disease with a poor prognosis if not diagnosed early. It can present with central nervous system (CNS) manifestations. The diagnosis of IVCBCL is difficult to make given its varied clinical manifestations and the lack of a specific diagnostic modality.Case presentation:We report an interesting case of IVLBCL presenting as bilateral strokes. The diagnosis was made by a random skin biopsy, which confirmed IVLBCL. The patient was treated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
0
5
0
1
Order By: Relevance
“…IVLBCL is rare; therefore, the majority of the data are case reports and expert panel opinions [1]. Although the true incidence of IVLBCL is unknown, some studies have reported that the incidence is less than one person per million [2][3]. The average age at the time of diagnosis is in the sixth and seventh decades of their lives, and men and women are affected equally [2,[4][5].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…IVLBCL is rare; therefore, the majority of the data are case reports and expert panel opinions [1]. Although the true incidence of IVLBCL is unknown, some studies have reported that the incidence is less than one person per million [2][3]. The average age at the time of diagnosis is in the sixth and seventh decades of their lives, and men and women are affected equally [2,[4][5].…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, such cases have been diagnosed during an autopsy [5,12]. To date, the diagnosis of IVLBCL relies on a combination of clinical features (multiple admissions and progressive symptoms) and pathological findings on biopsy [3]. The consensus on biopsy strategy is poor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunophenotyping of peripheral or CSF leucocytes does not appear to be a helpful technique in the diagnosis of this neoplasm, as it turns out negative in the majority of cases 3 (as disclosed in this case), due to the lack of circulating lymphoma cells. 9 There are no pathognomonic imagiological features in IVLBCL. Previous studies reported no brain lesions on MRI in half of patients with neurological manifestations, 5 however a recent study reported otherwise: the presence of brain lesions in MRI in patients without neurological symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…subaguda (27 %) y neuropatías periféricas o craneales (21 %) (5). Además, pueden observarse síntomas inespecíficos como fiebre, malestar general, pérdida de peso y astenia en 50 % de los casos (5,6).…”
Section: Discussionunclassified